Superfícies de Bianchi com ângulo de Chebyshev constante - BEZERRA, Adriano Cavalcante (2010)
The Bianchi surfaces belong to a class of surfaces with negative Gaussian curvature, discovered by generalization of Backlund transformation for surfaces with constant negative Gaussian curvature [3]. Today these areas are studied from the viewpoint of the theory of integrable systems. In this paper we study Bianchi surfaces parameterized by a Generalized Chebyshev net and show that such a surfaces with Chebyshev constant angle is a piece of a right helicoid, see [1].